The Meaning of Rabab Lyrics in South Pesisir : Figurative Language and Meaning Analysis - Jhoti Maysona, Jhoti Maysona; Aditiawarman, Mac (Jurnal Ilmiah Langue and Parole, 2024)
Barabab is a traditional art performance form that tells the story of Kaba by one or two performers accompanied by the playing of the rabab musical instrument (a type of stringed instrument similar to the violin). Barabab's performance lasted all night. Barabab performances are usually presented as a form of Bungo Alek (crowd decoration).This thesis aims to collect and analyze for majas metaphors, majas hyperbole, majas personification, majas irony and majas simili on the lyrics of rabab pasisia songs. The method used in this study is observation and interviews then qualitative research which is descriptive research and uses analysis. The theoretical basis is used as a guide so that the focus of the research is in accordance with the facts in the field.The theory in this study uses a theory from Gorys Keraf (2010: 112) about figurative language. The results showed that researchers found kind of figurative languages, they are (1)metaphora (2) hyperbole (3) personification (4) irony (5) simile.The conclusion of this study is that at least the use of irony majas because rabab songs generally tell about life, romance so that the use of irony or innuendo majas is not found.